1983
DOI: 10.1001/archneur.1983.04050080092023
|View full text |Cite
|
Sign up to set email alerts
|

Saccadic Latency Measurements in Dementia

Abstract: We measured saccadic latencies in patients with Alzheimer's dementia (AD) and other types of dementia. The saccad ic latencies for both groups were consid erably longer than those for age-matched controls. The prolongation was as exten sive in patients with other types of dementia as it was in those with AD. There was no correlation between latency and the severity of the dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1
1

Year Published

1986
1986
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 11 publications
2
17
1
1
Order By: Relevance
“…If the greater proportion of anticipatory responses on the simultaneous task in AD patients were solely a function of their memory impairment, one might expect that more severely demented patients might be more anticipatory. Neither predictive nor simultaneous task latency, however, was significantly correlated with measures of cognitive impairment in our patients, consistent with some studies [1, 8]but in contrast to others [4, 7]. The learning of a target sequence, seen in normal subjects when predictable stimuli are used, implies the preservation of visuomotor implicit memory (i.e., the next anticipated target position) in the presence of impaired explicit memory (i.e., amnesia for the instruction to follow the light) that characterises AD [33].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…If the greater proportion of anticipatory responses on the simultaneous task in AD patients were solely a function of their memory impairment, one might expect that more severely demented patients might be more anticipatory. Neither predictive nor simultaneous task latency, however, was significantly correlated with measures of cognitive impairment in our patients, consistent with some studies [1, 8]but in contrast to others [4, 7]. The learning of a target sequence, seen in normal subjects when predictable stimuli are used, implies the preservation of visuomotor implicit memory (i.e., the next anticipated target position) in the presence of impaired explicit memory (i.e., amnesia for the instruction to follow the light) that characterises AD [33].…”
Section: Discussionsupporting
confidence: 92%
“…Although abnormalities of both saccadic [1, 2, 3, 4, 5, 6, 7, 8, 9]and smooth pursuit [10, 11, 12]eye movements exist in Alzheimer’s disease (AD), neither prolonged saccadic latencies nor reduced pursuit gains per se are significant contributors to the eventually overwhelming disability experienced by the AD patient. Their importance lies instead in the information which ocular motor deficits can convey about dysfunction of the visuomotor pathways in the brain.…”
Section: Introductionmentioning
confidence: 99%
“…Another 10.6% of literature was dedicated to saccades, with contradictory results. Pioneer research showed increased latency (i.e., reaction time) of reflexive saccades, which was correlated [7] or not [8] with dementia severity. Five studies examining reflexive prosaccades and voluntary antisaccades (e.g., [9][10][11]) corroborated increased latency of the former (except [10]) and additionally evidenced more systematic deficit in the latter.…”
Section: Eye Movement Research In Presumed Admentioning
confidence: 91%
“…However, an early observation suggesting that prosaccadic latencies might prove to be a reliable index of dementia severity 13 was not confirmed. 7 Furthermore, results from studies looking at the saccadic gain and velocity in AD are controversial; some studies found impairment, 8,14 whereas other studies did not. 9,15 intrusions during attempted fixation; 11 and (2) visual capture by the target in the antisaccadic paradigm, 14,[17][18][19] in which the subject has to suppress a reflexive saccade to a peripheral target and execute an endogenously driven saccade to an equal and opposite location.…”
Section: Clinical Ocular Motor Manifestationsmentioning
confidence: 99%